(untitled) (TAJ: Journal of Teachers Association, 2009)
The term ‘Deliberate Self Harm’ (DSH) is often used to describe behaviors through which people inflict acute harm upon themselves with non-fatal outcome, when the behaviors are somewhat linked to, but do not result in death. This cross-sectional retrospective study included 66 subjects admitted with DSH in the Department of Medicine of Rajshahi Medical College Hospital during the period of January 2006 to July 2006. Among the respondents 57.57% were female and 42.42% were male, when they were mostly Muslims (89.39%) and only 10.61% were Hindus. As regards to occupation 46.96% were students, 30.30% were housewives and rest belong to others. 68.01% were in the age of 17-28 years. 50% were uneducated, 24.24% completed SSC and rests were in other classes. 42.42% were married, 45.45% were unmarried and others were either separated or divorced. DSH was mostly preceded by recent quarrel (34.84%), followed by poor interaction with parents (19.69%) and rejection of love (18.18%). The common adopted method of self-harm were ingestion of poisons (59.09%) and different self-medication (30.30%). 93.93% had the first attempt, 4.54% had second attempt and only 1 had the third attempt. The motivations were frustration (59.09%), making other feel guilty (25.75%) and to die (10.60%). Psychiatric diagnosis included relational problem (54.54%), major depressive disorder (34.84%), schizophrenia (4.54%) and adjustment disorder (3.03%). This study, in fact suggests a special need for the assessment of DSH and formulation of a comprehensive treatment approach. doi: 10.3329/taj.v21i2.3798 TAJ 2008; 21(2): 160-165